PPI-responsive esophageal eosinophilia cannot be distinguished from eosinophilic esophagitis by endoscopic signs. Issue 5 (May 2015) - Warners, Marijn J.; van Rhijn, Bram D.; Curvers, Wouter L.; Smout, Andreas J.P.M.; Bredenoord, Albert J.
<x xml:space="preserve">Abstract</x> Background Eosinophilic esophagitis (EoE) is a chronic antigen-mediated disease histologically characterized by eosinophil-predominant inflammation. One-third of patients respond to proton pump inhibitor (PPI) treatment; this group is identified as having PPI-responsive esophageal eosinophilia (PPI-REE). If we could predict the response to PPIs on the basis of endoscopic signs, futile treatment efforts and additional endoscopies to assess treatment response can be prevented. Objective To determine whether endoscopic signs can distinguish PPI-REE from EoE. Methods Endoscopic images of 30 EoE and 30 PPI-REE patients were included. Baseline characteristics were compared between groups. Complete clinical remission after a PPI trial for at least 8 weeks was classified as PPI-REE. Per patient, at least three depersonalized images were incorporated into a slideshow. These images were scored by two experienced endoscopists according to a validated classification system. Results Characteristics were highly comparable between EoE and PPI-REE patients. Endoscopic signs were similar and did not enable differentiation between EoE and PPI-REE [presence of: rings (P=0.893), white exudates (P=0.209), furrows (P=0.371), edema (P=0.554), crepe paper esophagus (P=1.000), and strictures (P=0.071)]. Conclusion Endoscopic signs at baseline endoscopy cannot distinguish EoE from PPI-REE before a PPI trial; the demographic and clinical characteristics in both groups are similar. Endoscopic features do not enable differentiation between PPI-REE and EoE.